Rancang Bangun Aplikasi E-CRM di Toko UD. Maju Jaya - Sari, Dira Purnama; Helmiah, Fauriatun; Syafnur, Afdhal (Institut Teknologi Garut, 2025)
Toko UD.Maju Jaya is a building shop that sells all kinds of building materials. Sales at UD Store. Maju Jaya is still experiencing problems, ranging from unstable sales to still using a manual system for recording and searching for products by customers is also inefficient because customers must come directly to the store. The purpose of this study is to create a web-based E-CRM system to make it easier for customers to place orders for building materials and increase operational efficiency. The research method used is the research and development method which consists of 6 stages starting from problem identification, data collection, analysis, system design, system testing to system implementation. The results of this study resulted in a web-based E-CRM system with features such as product details, shopping cart, online payment, chat so that it can maintain the store's relationship with customers and can also increase customer loyalty.